Posterior Reversible Encephalopathy Syndrome Induced by Mirtazapine Overdose: A Case Report - Min-Chiao Tsai; Wei-Hao Lin (Case Reports in Neurological Medicine)
Conclusion: Clinicians should recognize that mirtazapine overdose can cause serotonin syndrome and secondary PRES. Early identification and serotonin antagonism are crucial for recovery and prevention of sequelae.